2010
DOI: 10.1186/1476-4598-9-110
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bortezomib-adapted I-45 mesothelioma cells

Abstract: BackgroundBortezomib, a proteasome-specific inhibitor, has emerged as a promising cancer therapeutic agent. However, development of resistance to bortezomib may pose a challenge to effective anticancer therapy. Therefore, characterization of cellular mechanisms involved in bortezomib resistance and development of effective strategies to overcome this resistance represent important steps in the advancement of bortezomib-mediated cancer therapy.ResultsThe present study reports the development of I-45-BTZ-R, a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Flavonoids such as (−)-epigallocatechin-3-gallate (EGCG), apigenin, quercetin, kaempferol, myricetin have been reported to inhibit the proteasomal activity in a dose-and time-dependent manner both in vitro and in cultured leukemia cells with apigenin being among the most potent inhibitors [12]. This inhibition is associated with apoptosis induction in tumor cells, but not in normal, non-transformed cells [5]. Apigenin (4,5,7-trihydroxyflavone), a dietary phytochemical, is widely distributed in many fruits and vegetables, including parsley, onions, oranges, tea, chamomile, wheat sprouts and in some seasonings.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Flavonoids such as (−)-epigallocatechin-3-gallate (EGCG), apigenin, quercetin, kaempferol, myricetin have been reported to inhibit the proteasomal activity in a dose-and time-dependent manner both in vitro and in cultured leukemia cells with apigenin being among the most potent inhibitors [12]. This inhibition is associated with apoptosis induction in tumor cells, but not in normal, non-transformed cells [5]. Apigenin (4,5,7-trihydroxyflavone), a dietary phytochemical, is widely distributed in many fruits and vegetables, including parsley, onions, oranges, tea, chamomile, wheat sprouts and in some seasonings.…”
mentioning
confidence: 97%
“…the chymotrypsin-like (β-5 subunit), the trypsin-like (β-2 subunit) and the caspase-like (β-1 subunit) activities [5]. Chymotrypsin-like activity is the rate-limiting step of protein degradation [6].…”
mentioning
confidence: 99%
“…It has been previously reported that Noxa expresses in colorectal cancers, malignant melanomas and ameloblastomas [36,37,38,39], and that it is involved in the mechanism of action of the anticancer agents bortezomib and pemetrexed [40,41,42,43,44,45,46,47]. However, the expression of Noxa in mesothelioma cells has so far not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…59,60 Differences in underlying resistance mechanisms have not been convincingly elucidated. 2,[61][62][63][64][65][66][67] Recently, upregulation of P-glycoprotein could be demonstrated after CFZ, suggesting that drug transport may contribute to resistance. 68,69 …”
Section: Cfz Resistancementioning
confidence: 99%